PERSEPSI GURU MENGENAI PENGEMBANGAN INSTRUMEN PEMECAHAN MASALAH DALAM MATERI SEGITIGA DI KELAS VII SMP - Riyanti, Vera; Rif at, Mohamad; Jami, Yulis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe instrument for problem solving given to students was only a problem solving that demands routine procedures and the instrument was not in accordance with the problem solving indicators and the level of Bloom?s taxonomy. This study aimed to explain the teacher's perceptions regarding the instruments to solve the problem in triangular material at Junior High School. The study was used the development design which the instrument type as development research. The samplesof this study were 10 mathematics teachers. According to the validity test of Product Moment correlation obtained 75.7% and 81.1%. The accuracy of the teacher instruments perception through the instruments ability problem solvingdeliver to Bloom's taxonomy, triangular material at Junior High School had high validity. The results of the questionnaire used the average calculation obtained of 82% and 70,6% which mean that mathematics teachers strongly agree that the instrument of problem solving developed by researcher properly with Bloom's cognitive taxonomy level and mathematics teachers have never provided problem solving instruments like the researcher were develop for the students. Keywords: Problem Solving, Teacher Perception